2020
DOI: 10.3389/fonc.2020.01318
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Testing for Somatic and Germline BRCA1/BRCA2 Variants in Ovarian Cancer Patients in the Context of Strong Founder Effects

Abstract: Deleterious variants in the BRCA1/BRCA2 genes and homologous recombination deficiency (HRD) status are considered strong predictors of response to poly (ADP-ribose) polymerase (PARP) inhibitors (PARPi). The introduction of PARPi in clinical practice for the treatment of patients with advanced ovarian cancer imposed changes in the molecular diagnosis of BRCA1/BRCA2 variants. BRCA1/BRCA2 tumor testing by next-generation sequencing (NGS) can detect simultaneously both somatic and germline variants, allowing the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…An acquired somatic BRCA variant (not present in the germline) was detected in 11/169 (6.5%) of concurrently dual‐tested patients in this study with the majority (72.7%, 8/11) of the variants identified in BRCA1 . This is in‐line with other studies (Table 2) that have reported similar somatic variant detection rates of 4.1–7.1% 15–17 . The acquired somatic variant rate represents a significant proportion of patients that are eligible for PARPi treatment that would not be identified through germline screening alone and highlights the importance of access to tumour testing services for this population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…An acquired somatic BRCA variant (not present in the germline) was detected in 11/169 (6.5%) of concurrently dual‐tested patients in this study with the majority (72.7%, 8/11) of the variants identified in BRCA1 . This is in‐line with other studies (Table 2) that have reported similar somatic variant detection rates of 4.1–7.1% 15–17 . The acquired somatic variant rate represents a significant proportion of patients that are eligible for PARPi treatment that would not be identified through germline screening alone and highlights the importance of access to tumour testing services for this population.…”
Section: Discussionsupporting
confidence: 90%
“… 9 , 10 , 11 , 12 , 13 , 14 Studies in patients with serous ovarian cancer have shown that a further 4.1–7.1% of patients’ tumours harbour an acquired BRCA pathogenic variant (Table 2 ). 15 , 16 , 17 This highlights a significant proportion of this patient population that may be more responsive to PARPi maintenance therapy and demonstrates the clinical need to have effective genetic screening strategies in National Health Service (NHS) laboratories to identify these patients in a timely manner.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, genetic testing (somatic and germline) for all women diagnosed with OC is recommended ( 6 ). Comprehensive genetic testing is usually performed in formalin fixed paraffin embedded (FFPE) tumor samples and blood samples are used to verify whether the variants found in tumor are germline or somatic and to look for germline exon rearrangements ( 7 ). FFPE tumor samples are often used for molecular profiling, as it is widely available and easy to use and to store.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of OC, there are other challenges, such as the difficulty of performing tumor biopsy due to anatomical limitations or risk of spillage ( 10 ), so the majority of tumor samples from OC patients are obtained at the time of the surgery. However, these samples may not be the most suitable for tumor molecular profiling, as several OC patients are treated with chemotherapy before debulking surgery, which can modify the tumor genetic profile as the result of mutational shifts induced by chemotherapy ( 7 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between PARP inhibitor efficacy and BRCA mutations was further investigated in original research by Peixoto et al who sought to determine the frequency of somatic and germline BRCA mutations in non-mucinous ovarian cancers, with focus on those with Portuguese ancestry ( 7 ). They discovered pathogenic variants in 19.3% of patients (13.3% germline, 5.9% somatic), with higher prevalence in tumors with high-grade serous morphology.…”
mentioning
confidence: 99%